Characterisation of pain in people with hereditary neuropathy with liability to pressure palsy - Beales, Darren; Fary, Robyn; Little, C.; Nambiar, S.; Sveinall, H.; Yee, Y.; Tampin, B.; Mitchell, T. (Springer Medizin, 2017)
Hereditary neuropathy with liability to pressure palsy (HNPP) has historically been considered a pain-free condition, though some people with HNPP also complain of pain. This study characterised persistent pain in people with HNPP. Participants provided cross-sectional demographic data, information on the presence of neurological and persistent pain symptoms, and the degree to which these interfered with daily life. The painDETECT and Central Sensitization Inventory questionnaires were used to indicate potential neuropathic, central sensitisation and musculoskeletal (nociceptive) pain mechanisms. Additionally, participants were asked if they thought that pain was related to/part of HNPP. 32/43 (74%) subjects with HNPP had persistent pain and experience this pain in the last week. Of those with pain, 24 (75%) were likely to have neuropathic pain and 27 (84%) were likely to have central sensitisation. All 32 participants felt that their pain could be related to/part of their HNPP. Significant negative impact of the pain was common. Pain characterisation identified neuropathic pain and/or central sensitisation as common, potential underlying processes. Pain may plausibly be directly related to the underlying pathophysiology of HNPP. Further consideration of including pain as a primary symptom of HNPP is warranted.